Strossmayerana in the English sources : Acton, Gladstone, Newman and Strossmayer - Živić, Tihomir (Array, 2018)
The paper deals with the friendship of Josip Juraj Strossmayer, the »First Son of His Homeland,« with the British John Emerich Edward Dalberg-Acton, 1st Baron Acton, KCVO DL, a known politician, man of letters, and the »Magistrate of History,« and ideational relation to John Henry Newman, Cong. Orat., the »Augustine of the Modern World.« Analyzed is a correspondence, mostly untranslated heretofore, of the Đakovo »vladika« (that is, episcope), as he titled himself frequently, with William Ewart Gladstone, FRS, FSS, the »People’s William« and the then British Prime Minister, especially in the 1876‒1892 timespan, and the new realizations on Strossmayer’s role in the rebirth of the Croatian culture, his attitude toward the South Slav question and Pan-Slavism, as well as a neo-historical study of the outreach of his speech at the First Vatican Council, have been exploratorily elucidated, with an evaluatory interpretation, from an Anglo-American viewpoint. Thus, Strossmayer’s intercession of a federal-state system, understanding for a unification of the Kingdoms of Dalmatia and Croatia, and a guarantee that the Croatian language be introduced in the then official usage, has also been revalorized, while his cultural significance has been described as a realization of the renaissance Latin term of a »universal man.« All these determinants describe his cultural importance equally cognitively, for just a few of the Croatian 19th-century dignitaries have incorporated it by their influential personalities.